THE BALANCED SCORECARD AS A STRATEGIC PERFORMANCE CONTROL TOOL AND ITS LINK TO THE ECONOMIC PROFIT MEASUREMENT- EVA AND MVA: A LITERATURE REVIEW - Anbalagan Krishnan; R. Ravindran (Bina Nusantara University, 2010)
The organizational performance measurement and control system is vital to sustain the business in all economic environments. Organization requires a control system that measures the performance strategically. This paper gathers the literature discussion of one such popular integrated strategic performance control system, the balanced scorecard approach (BSC). The discussion focuses on BSC approach on facilitating the implementation of organizational strategic and its link to the economic profit measures. Two popular economic profit measures, the Economic Value Added (EVA) and Market Value Added (MVA) are discussed in detail from various researchers point of view. The paper highlights the difference between these two measures and difference with the Return on Investment (ROI). The limitation of the economic profit measure is also highlighted in the discussion. As conclusion the link between the BSC strategic performance control tool and the economic profit measures are noted. This paper provides detailed discussions of both BSC strategic tool and economic profit measures based on literature review.